The Implementation of Problem-Based Learning Strategy (PBLS) in Arabic Language Learning in Grade VIII at MTs Negeri 4 East Tanjung Jabung - Putri Sulistia Wati; Afriana Santosa (FKIP, Universitas Palangka Raya, 2026)
This study aims to describe the implementation of the Problem-Based Learning Strategy (PBLS) in Arabic language learning for eighth-grade students at MTs Negeri 4 East Tanjung Jabung, as well as identify supporting factors, inhibiting factors, and efforts to overcome those obstacles. This research employed a descriptive qualitative approach using observation, interviews, and documentation techniques. The research subjects included the principal, Arabic language teacher, and eighth-grade students. The findings revealed that PBLS was implemented through stages of problem presentation, information identification, group discussion, presentation, and evaluation. This strategy improved students’ active participation, critical thinking skills, communication abilities, and understanding of Arabic learning materials. Supporting factors included teacher professionalism, adequate facilities and infrastructure, and support from the school environment. Inhibiting factors included students’ low reading interest, limited instructional time, and differences in students’ characteristics and abilities. Efforts to overcome these obstacles involved providing motivation, forming heterogeneous groups, effective time management, and utilizing simple and engaging learning media. Therefore, PBLS is considered effective in Arabic language learning because it enhances both the learning process and student learning outcomes.